Risk of Herpes Zoster Prior to and Following Cancer Diagnosis and Treatment: A Population-Based Prospective Cohort Study. (13th December 2018) - Qian, Jiahui; Heywood, Anita Elizabeth; Karki, Surendra; Banks, Emily; Macartney, Kristine; Chantrill, Lorraine; Liu, Bette
Abstract: Background: Information on the risks of herpes zoster (zoster) preceding a cancer diagnosis and the role of cancer treatment on risk is limited. Methods: This was a prospective cohort of 241497 adults, with mean age 62.0 years at recruitment (2006–2009), linked to health datasets from 2006 to 2015. The relation between cancer diagnosis, treatment, and zoster risk was analyzed using time-varying proportional hazards models. Results: Over 1760 481 person-years of follow-up, 20286 new cancer diagnoses and 16350 zoster events occurred. Participants with hematological and solid cancer had higher relative risks of zoster than those without cancer (adjusted hazard ratio [aHR], 3.74 [95% confidence interval CI, 3.11–4.51] and 1.30 [95% CI, 1.21–1.40], respectively). Compared to those without cancer, zoster risk was also elevated prior to a hematological cancer diagnosis (aHR for 1–2 years prior, 2.01 [95% CI, 1.31–3.09]), but this was not the case for solid cancers (aHR for 1–2 years prior, 0.90 [95% CI, .75–1.07]). Compared to those without cancer, zoster risk among participants with solid cancers receiving chemotherapy was greater than in those without a chemotherapy record (aHR, 1.83 [95% CI, 1.60–2.09] and 1.16 [95% CI, 1.06–1.26], respectively). Conclusions: For hematological cancer, increases in zoster risk are apparent in the 2 years preceding diagnosis and treatment; for solid organ cancers, the increased risk appears to be largely associated with receipt of chemotherapy. Abstract : For hematological cancers, a substantial proportion of the subsequent increased zoster risk appears to be related to immunosuppression associated with the cancer itself; for solid organ cancers, the risk appears to be largely related to the immunosuppression from chemotherapy.